HANIF DALAM KONSEP AL QURAN - Bakri, Mubarak (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2019)
This article discusses the main problem that is how the nature of hanif in the view of the Koran, both in terms of forms of expression, types, and their influence in social life. The word hanif is usually interpreted as "straight" or "inclined toward something". This word was originally used to describe the soles of the feet and their slope to the soles of their partners, the right leaning towards the left, and the left leaning towards the right. This makes humans able to walk straight. That straightness makes the pedestrian not lean to the left, nor to the right. Hanif describes a heart that is clean from envy and envy, a heart that is inclined towards monotheism and far from shirk, a heart that is in love with the hereafter and hates the charming world, a heart that is clean from lust that can hinder itself with God's prohibition, a heart that is far from doubtful which can prevent him from receiving the message of God in the Koran. So the person who has the soul of hanif is someone who is soft-hearted as soft as cotton, smooth as smooth as a hair.